1990
DOI: 10.1063/1.458499
|View full text |Cite
|
Sign up to set email alerts
|

The morphology of symmetric diblock copolymers as revealed by neutron reflectivity

Abstract: The specular reflectivity of neutrons has been used to characterize quantitatively the microphase separated morphology of symmetric, diblock copolymers of polystyrene (PS), and polymethylmethacrylate (PMMA), as a function of the total molecular weight of the copolymer where either block is perdeuterated. It is shown that the hyperbolic tangent function, as opposed to a linear or cosine-squared function, most closely describes the concentration gradient at the interface between the lamellar copolymer microdomai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
327
2
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 365 publications
(362 citation statements)
references
References 68 publications
32
327
2
1
Order By: Relevance
“…We find several studies reported on the interfacial properties in terms of interdiffusion at the interface, [22][23][24][25][26] interfacial tension, [27][28][29][30] and interface width, 21,[31][32][33][34] and so forth in polymer blends. The magnitude and behavior of interface width with varying molecular weight, temperature, and film thickness have also been studied using the small angle neutron scattering, neutron reflectometry, 27,28,[33][34][35] small angle X-ray scattering, differential scanning calorimetry (DSC), 26 transmission electron microscopy, 30 and so forth with varying success.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…We find several studies reported on the interfacial properties in terms of interdiffusion at the interface, [22][23][24][25][26] interfacial tension, [27][28][29][30] and interface width, 21,[31][32][33][34] and so forth in polymer blends. The magnitude and behavior of interface width with varying molecular weight, temperature, and film thickness have also been studied using the small angle neutron scattering, neutron reflectometry, 27,28,[33][34][35] small angle X-ray scattering, differential scanning calorimetry (DSC), 26 transmission electron microscopy, 30 and so forth with varying success.…”
Section: Introductionmentioning
confidence: 97%
“…It is also defined as the region between the adjacent microphases or monomers. 21 In the bilayer polymer thin films, despite the fact that the two layers are immiscible, a narrow region of overlap between two polymers will form. An infinitely sharp interface cannot be formed in any blend system, rather one can say a transition region called the interphase or interface width will be created wherein polymer chain density of one type gradually decreases as the chain density of second type increases.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the PS-b-PMMA thin film as-spincoated was too thick to form a flat self-assembled PS-b-PMMA film. According to the literatures [24][25][26], the mean value of PMMA cylinder spacing (L 0 ) has a relationship of L 0 = M n 0.66 with total molecular weight (M n ). The empirical relationship suggested that the PMMA cylinder spacing of PS-b-PMMA used in this study was L 0 = 27.5 nm.…”
Section: Preparation Of Flat Ps-b-pmma Thin Films Without Terrace Islmentioning
confidence: 99%
“…This example is inspired by an experimental system studied by Anastasiadis, Russell, Satija & Majkrzak (1990) by the neutron reflectivity technique. The system consists of a film of a symmetric poly(styreneb-methylmethacrylate) diblock copolymer on a silicon substrate, with the styrene block perdeuterated.…”
Section: ½-1ayer Diblock Copolymermentioning
confidence: 99%
“…The system consists of a film of a symmetric poly(styreneb-methylmethacrylate) diblock copolymer on a silicon substrate, with the styrene block perdeuterated. In the experimental work of Anastasiadis et al (1990), a profile with 3½ periods was determined by a least-squares fit of a box model. Our simulated data for a similar profile, with 3% Gaussian noise and smeared by instrumental resolution, is shown in the upper part of Fig.…”
Section: ½-1ayer Diblock Copolymermentioning
confidence: 99%